Effects of the Chinese Herb Medicine Formula "She-Xiang-Yu-Hong" Ointment on Wound Healing Promotion in Diabetic Mice. (29th January 2022) - Li, Qingjie; Liu, Xinjun; Yang, Shihui; Li, Chunrun; Jin, Wei; Hou, Weiwei
Abstract : Wound healing in diabetic patients is a difficult problem to be solved at present. In addition, patients with diabetes have an increased risk of postoperative wound complications. "She-Xiang-Yu-Hong" (SXYH) ointment is a type of traditional Chinese medicine (TCM) compound used to treat wounds. Over the past few years, SXYH has been applied in the Affiliated Hospital of Chengdu University of TCM (Chengdu, China) for the treatment of diabetic foot infections and bedsores, whereas there has been rare research on the effect of SXYH ointment on wound healing. In this study, SXYH ointment was first applied to streptozotocin (STZ)-triggered diabetic ICR mice (4–6 weeks, 20 ± 2 g) to observe the accelerated wound healing and the shortened wound healing period. As indicated by the histology and biochemistry analyses of skin biopsies, the wounds treated using SXYH ointment showed an increase in the granulation tissue. Moreover, SXYH also modulated the inflammation response by regulating affinity proinflammatory cytokines release (e.g., IL-6 and TNF- α ). Furthermore, SXYH ointment obviously improved collagen fiber deposition and tissue on the wound surface. On the whole, this study indicated that SXYH ointment could accelerate wound healing, promote blood vessel formation, and suppress inflammations. Thus, the clinical potential of SXYH ointment was demonstrated in the treatment of diabetes and refractory wounds.